A Concept Analysis of Disturbed Body Image in Bariatric Surgery Patients. Issue 1 (24th July 2018) - Perdue, Tamara O.; Schreier, Ann; Neil, Janice; Carels, Robert; Swanson, Melvin
Abstract : PURPOSE: This article describes the concept of disturbed body image in bariatric surgery patients. METHOD: Walker and Avant's (2011) method of concept analysis is used in this study. FINDINGS: After bariatric surgery, the patient's body may change more rapidly than their allocentric ("inside, lived") view of themselves, leading to physical and psychosocial sequelae. CONCLUSION: If not prepared physically and psychologically for body image challenges after bariatric surgery, patients may experience disturbed body image in the postoperative phase. IMPLICATIONS FOR NURSING PRACTICE: Understanding the concept of disturbed body image in postoperative bariatric surgery patients may allow health providers to provide preoperative teaching and preparation, as well as postoperative interventions to create congruence between the patient's internal and external selves.